2018
DOI: 10.4103/aian.aian_228_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intracerebral hemorrhage in acute stroke patients receiving intravenous recombinant tissue plasminogen activator

Abstract: Background:Symptomatic Intracerebral hemorrhage (sICH) is a serious complication of recombinant tissue-plasminogen activator (rt-PA) therapy for acute ischemic stroke (AIS).Objective:To estimate the prevalence and predictors of sICH in patients after receiving IV rt-PA for AIS.Material and Methods:Consecutive patients of AIS thrombolysed between January 2010 and June 2016 in a University hospital in Hyderabad (India) were studied prospectively for sICH and it's various variables compared with the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The increased risk of sICH after intravenous thrombolysis in high glucose level group compared with non-high glucose level points to an effect of blood glucose levels on the risk of sICH. Previous studies have also shown that admission blood glucose is one of the predictors of sICH (22)(23)(24), even after controlling for HbA1c (25). Possible mechanisms include higher blood glucose impairing cellular metabolism, reducing vascular reactivity, increasing blood-brain barrier permeability and exacerbating acidosis in reperfused brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of sICH after intravenous thrombolysis in high glucose level group compared with non-high glucose level points to an effect of blood glucose levels on the risk of sICH. Previous studies have also shown that admission blood glucose is one of the predictors of sICH (22)(23)(24), even after controlling for HbA1c (25). Possible mechanisms include higher blood glucose impairing cellular metabolism, reducing vascular reactivity, increasing blood-brain barrier permeability and exacerbating acidosis in reperfused brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a contraindication for thrombolytic therapy, prolonged symptom/needle time, high baseline NIHSS score, hypertension, and diabetes history have been shown to be the most significant predictors of the risk for thrombolysis-related symptomatic ICH. [ 31 ] atrial fibrillation and cardioembolic strokes have been linked to increased risk and poor prognosis of thrombolysis-related ICH. [ 32 - 34 ] In our study, the presence of diabetes among the vascular risk factors of the two groups was remarkably higher in the standard-dose IV r-tPA group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be explained by the higher proportion of patients with small vessel disease in CHs than in the other two hospital levels, 43.8% vs. 35.6% vs. 31.5%, as shown in Table 1 . As a result, the CH group had lower initial NIHSS than the others, leading to higher odds of intracerebral hemorrhage [ 12 ]. Patients with acute ischemic stroke with higher initial NIHSS had higher odds of symptomatic intracerebral hemorrhage than those with lower NIHSS (16.53 vs. 10.19; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%